The Importance of Gene Duplication and Domain Repeat Expansion for the Function and Evolution of Fertilization Proteins - Rivera, Alberto M.; Swanson, Willie J. (Frontiers in Cell and Developmental Biology, 2022)
The process of gene duplication followed by gene loss or evolution of new functions has been studied extensively, yet the role gene duplication plays in the function and evolution of fertilization proteins is underappreciated. Gene duplication is observed in many fertilization protein families including Izumo, DCST, ZP, and the TFP superfamily. Molecules mediating fertilization are part of larger gene families expressed in a variety of tissues, but gene duplication followed by structural modifications has often facilitated their cooption into a fertilization function. Repeat expansions of functional domains within a gene also provide opportunities for the evolution of novel fertilization protein. ZP proteins with domain repeat expansions are linked to species-specificity in fertilization and TFP proteins that experienced domain duplications were coopted into a novel sperm function. This review outlines the importance of gene duplications and repeat domain expansions in the evolution of fertilization proteins.